Study On Recovery And Utilization Of Valuable Components From Glycerol Residue - Yong, Kuang Chih (2002)
The Malaysian palm-based oleochemicals industry is growing rapidly and producing an increasing array of products like fatty acid methyl esters, fatty alcohols and glycerine. In the production of these oleochemicals, by-products are produced in which many of them are potentially useful. One of the by-products is glycerol residue which is generated by a glycerol refining plant (the glycerine source is from methanolysis of palm kernel oil). Glycerol residue is a waste under Schedule Waste SI8I of the Environmental Regulations in Malaysia. Currently, this waste is disposed off in landfills with the cost of about RM700.00/tonne. This research was therefore undertaken to characterize the glycerol residue, and to recover and utilize its valuable components. It was found that thirteen batches of glycerol residue, GRI to GR13, showed variation in the contents of glycerol, ash, moisture and matter organic non-glycerol (MONG). Salt (63.7%), glycerol (19.7%) and MONG (12.9%, mainly as soap) were the three main